Peran Komunikasi Organisasi dalam Meningkatkan Kinerja Pengurus Desa Dahian Tambuk Kecamatan Mihing Raya Kabupaten Gunung Mas Provinsi Kalimantan Tengah: The Role of Organizational Communication in Improving the Performance of Village Officials in Dahian Tambuk, Mihing Raya District, Gunung Mas Regency, Central Kalimantan Province - Hidayat, Rahmat (Pencerah Publik, 2024)
The role of communication in an organization is very important, because it will help to establish good relationships and good coordination between fellow members in achieving organizational goals, besides that, organizational communication will also have an impact on increasing the performance motivation of members of the organization. In this research, researchers used descriptive qualitative research. The data collection techniques used are: 1) observation, 2) interviews, 3) documentation. The research results show that organizational communication in Dahian Tambuk Village is good, but one of the obstacles experienced is an unstable network. The suggestion in this research is for village office administrators to overcome one of the existing problems, namely to use wireless networks (Wi-Fi) so that communication can run smoothly with each other and can also provide information more quickly to the community.